2017
DOI: 10.1063/1.4979712
|View full text |Cite
|
Sign up to set email alerts
|

Cheap but accurate calculation of chemical reaction rate constants from ab initio data, via system-specific, black-box force fields

Abstract: Building on the recently published quantum-mechanically derived force field (QMDFF) and its empirical valence bond extension, EVB-QMDFF, it is now possible to generate a reliable potential energy surface for any given elementary reaction step in an essentially black box manner. This requires a limited and pre-defined set of reference data near the reaction path and generates an accurate approximation of the reference potential energy surface, on and off the reaction path. This intermediate representation can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Admittedly, employing the full electron density carries with it a considerable computational cost; nevertheless, it is useful to develop such frameworks, considering that more optimal algorithms could follow. Previously, we had shown that the electron density could be used in a self-consistent manner to train a system-specific density functional (akin to a system-specific force field 52 ) using a mapping from the external potential to the electron density and a second map of the density to the total energy 53 . Rather than delivering a solution to the KS equations, the first map (denoted the ML-HK map) bypasses the KS equations in a manner that is akin to solving the original Hohenberg-Kohn functional differential equation 54 .…”
mentioning
confidence: 99%
“…Admittedly, employing the full electron density carries with it a considerable computational cost; nevertheless, it is useful to develop such frameworks, considering that more optimal algorithms could follow. Previously, we had shown that the electron density could be used in a self-consistent manner to train a system-specific density functional (akin to a system-specific force field 52 ) using a mapping from the external potential to the electron density and a second map of the density to the total energy 53 . Rather than delivering a solution to the KS equations, the first map (denoted the ML-HK map) bypasses the KS equations in a manner that is akin to solving the original Hohenberg-Kohn functional differential equation 54 .…”
mentioning
confidence: 99%
“…In contrast, if the choice was to use coupling terms that do not depend on mk but other degrees of freedom such as spatial coordinates (see refs. [40][41][42][43][44][45][46], we cannot discern a clear logic to derive an expression for σ EVB , which might explain the fact there is no evidence of any previous reported method to compute the stress tensor using EVB.…”
Section: Ijmentioning
confidence: 81%
“…To overcome these limitations, a combination of Gaussian functions were proposed to model the coupling terms. 45 This methodology offers a promising route for calibration and development of EVB potentials, and provides a suitable framework for future applications of the EVB extension proposed in this work.…”
Section: Coupling Termsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, NMA with the explicit solvent approach cannot be conveniently employed for studying multicomponent solvents since achieving appropriate sampling of a canonical ensemble in this way is challenging. Consequently, theoretical evaluation of k 3−4 in saline water is achieved via NMA with the implicit solvent approach [21] as well as path integral molecular dynamics [22,23]. The latter method also allows studying the anharmonicity impacts on the calculated partition functions.…”
Section: Introductionmentioning
confidence: 99%